Effect of antibiotics on the growth and maturation in goldfish (Carassius auratus) - Ahilan, B; Jeyaseelan, M J Prince (Indian Journal of Fisheries, 2011)
The investigation was aimed at determining the effect of antibiotics on the growth and maturation of goldfish. The fishes were stocked in rectangular cement tanks and fed with artificial feed incorporated with antibiotics (virginiamycin and oxytetracycline) at three different concentrations. Among the doses tested for virginiamycin 50 ppm treatment showed highest response for both maturation and growth. The mean weight increment for individual fish was observed to be 4.409 g. In oxytetracycline treatment 150 ppm gave positive result for total weight gain of the fishes.